[Niṣāb al-ṣibyān...etc., ca. 1222, i.e. 1807]. - Farāhī, Abū Naṣr Muḥammad Badr al-Dīn.; Nuttall, Frank E.; Bābā Valad Āghā Shihāb; Vaṭvāṭ, Rashīd al-Dīn Muḥammad ibn Muḥammad; Mīrzā Muḥammad Ismāʻīl. (1807)
Abū Naṣr al-Farāhī's versified Arabic-Persian vocabulary followed by a collection (majmūʻah) of poetry in Persian, beginning with rubāʻīyāt and including works attributed to Mīrzā Muḥammad Ismāʻīl and Rashīd al-Dīn Vaṭvāṭ, somewhat haphazardly copied toward the end.
Shelfmark: Ann Arbor, University of Michigan, Special Collections Research Center, Isl. Ms. 866
Origin: As appears in colophon on fol.38a, first work copied by Bābā [?] Valad Āghā Shihāb. Copying finished Jumādá I 1222 [July-August 1807]. Anthology lacks a formal colophon, though a few dates appear (1206 [1791 or 2], 1211 [1796 or 7] p.241), likely also early 19th century.
Accompanying materials: a. Slip in hand of Meredith-Owens marked "MO 11" describing contents and suggested dating reads "MO 11 Niṣāb al-ṣibyān of Abū Naṣr Farāhī. A rhymed Arabic-Persian vocabulary. Followed by a verse anthology and the Dīvān of Mīrzā Muḥammad Ismāʻīl of Shīrāz. Undated but probably XIXth century" b. Slip reading "Persian MSS (Heyworth-Dunne?) with Meredith-Owens notes" c. Slip reading "counted for 1968/69 Annual Report"
Former shelfmark: Mich. Isl. Ms. temp. no. 15
Binding: Pasteboards (quite spongy) covered in brown (with orange tones) leather ; Type III binding (without flap) ; board linings in black leather ; white and pink threads ; two sewing stations ; endbands in yellow with a chevron pattern ; in poor condition, with much wear, repair on spine ; lower cover has fully detached at spine ; extensive page repairs at beginning of ms. unfortunately obscure text in many places and make transcription of incipit difficult ; quite soiled with dirt, wax, food, and other stains ; housed in box for protection.
Keywords: Manuscripts, Persian / Michigan / Ann Arbor.; Persian poetry. / http://id.loc.gov/authorities/subjects/sh85100084; Persian language / Versification. / http://id.loc.gov/authorities/subjects/sh2008109073; Arabic language / Glossaries, vocabularies, etc. / http://id.loc.gov/authorities/subjects/sh2007101227; Persian language / Glossaries, vocabularies, etc. / http://id.loc.gov/authorities/subjects/sh2010105554